Modified routine for decreasing numeric oscillations at associations of lumped elements - Prado, Afonso Jose do [UNESP]; Lessa, Leonardo da Silva [UNESP]; Monzani, Rafael Cuerda; Bovolato, Luiz Fernando [UNESP]; Pissolato Filho, Jose (Elsevier B.V., 2014)
Some changes in the application of the numeric trapezoidal integration are analyzed for applications considering pi circuits. It is considered numeric and computational proceedings for improving the numeric results obtained with associations of pi circuits. In numeric integration solutions of the linear systems, it is common to represent these associations of pi circuits by only one matrix. This representation introduces undesirable numeric oscillations in simulations of the dynamics of wave propagation in electrical systems. The proposed changes improve the results of application of cascades of pi circuits associated to the trapezoidal integration, avoiding that the numerical oscillations, or Gibb's oscillations, have high values and are slowly damped. For the carried out simulations, different number of pi circuits and voltage sources are checked, confirming the reduction of the influence of the numeric oscillations on the obtained results. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Eigenvalues and eigenfuctions; Electromagnetic transient analyses; Linear systems; Numerical analysis; State space methods; Transmission lines